Contribuição do uso de modelagem de processos de negócios na implementação de ERP de fornecedores nacionais em pequenas e médias empresas. - Silva, Fernanda Pereira Carneiro da (2005)
The purpose of this study is to investigate the implementation of Enterprise Resource Planning (ERP) in small and medium enterprises (SME) in whom it says respect to the Business Processes Modeling (BPM) use. Until little time behind, the SME were not using conventionals of system ERP. Observed the BPM use, for the suppliers, and verified it influence in the integration of the internal processes of the business of the customer. Due to the fact that the utilization of (ERP) in small and medium enterprises is a recent issue, most of the reviewed literature was found in articles and books addressed to big companies. Substantive matters on business processes modeling (BPM) were found in international articles and books. Hardly ever, BPM, ERP or SME issues were discussed in the same article or book. Therefore, for this inquiry, one searched the information in the suppliers and customers of ERP, by means of differentiated questionnaires, that had been applied in the national supplying greaters of systems and in some customers of the system of these suppliers. This research contributed with the systematization of theoretical information regarding the concepts of BPM and in the vision of the ERP sustem in SME. With the carried through research of field, it made possible to get real information of the main characteristics of implementation with the use of the BPM for the suppliers and of its interference in the internal processes of business of some using customers, showing indications of that the BPM contributes for a bigger integration of the internal processes of business and that this option is made by the customer and that all the suppliers of this research had conditions to take care of it.